Virus genotyping by massive parallel amplicon sequencing: adenovirus and enterovirus in the Norwegian MIDIA study - Cinek, Ondrej; Kramna, Lenka; Mazankova, Karla; Kunteová, Kateřina; Chudá, Kateřina; C J Claas, Eric; Stene, Lars C; Tapia, German (Journal of medical virology, 2019)
OBJECTIVES: Direct genotyping of adenovirus or enterovirus from clinical material using polymerase chain reaction (PCR) followed by Sanger sequencing is often difficult due to the presence of multiple virus types in a sample, or due to varying efficacy of PCR amplifying the capsid gene on the background of foreign nucleic acids. Here we present a simple protocol for virus genotyping using massive parallel amplicon sequencing. METHODS: The protocol utilized a set of 16 tailed degenerate primers flanking the seventh hypervariable region of the adenovirus hexon gene and 9 tailed degenerate primers targeted to the proximal portion of the enterovirus VP1 gene. Subsequent addition of dual indices enabled simultaneous sequencing of 384 different samples on an Illumina MiSeq instrument. Downstream bioinformatic analysis was based on remapping to a set of references representative of the presently known repertoire of virus types. RESULTS: After validation with known virus types, the sequencing method was applied on 301 adenovirus-positive samples and 350 enterovirus-positive samples from a longitudinally collected series of stools from 83 children aged 3 to 36 months. We detected 7 different adenovirus types and 27 different enterovirus types. There were 37 (6.2%) samples containing more than one genotype of the same viral genus. At least one dual infection was experienced by 23 of 83 (28%) of the children observed over the 3 years' observation period. CONCLUSIONS: Amplicon sequencing with a multiplex set of degenerate primers seems to be a rapid and reliable technical solution for genotyping of large collections of samples where simultaneous infections with multiple strains can be expected.
Keywords: Enterovirus Infections; genotypizační techniky; Male; Adenoviridae; Child, Preschool; longitudinální studie; Adenoviridae Infections; Genotype; Enterovirus; adenovirus; výpočetní biologie; genotype; Infant; Sequence Analysis, DNA; sekvenční analýza DNA; Norway; mužské pohlaví; DNA Primers; infants; předškolní dítě; massive parallel sequencing; Animals; lidé; ženské pohlaví; virus type; Humans; zvířata; kojenec; DNA primery; adenovirové infekce; Longitudinal Studies; genotyp; Norsko; enterovirus; Female; Genotyping Techniques; enterovirové infekce; Computational Biology